Ascorbate as Prophylaxis and Therapy for COVID-19—Update From Shanghai and U.S. Medical Institutions. (July 2020) - Cheng, Richard Z; Kogan, Mikhail; Davis, Devra
Background: No validated treatments have been identified for the COVID-19 pandemic virus; several are currently in randomized clinical trials. Diagnostic instruments are rapidly evolving. Symptoms range from those of a common cold to acute respiratory distress syndrome (ARDS), to sepsis arising from the flood of inflammatory bacterial and viral pathogens in the blood. Mortality generally arises from cytokine storms of uncontrolled inflammation, oxidative injury, and damage to the alveolar-capillary barrier, with secondary bacterial infection. To address the indisputably urgent need for therapeutics for COVID-19, a specialized interdisciplinary medical panel convened in Shanghai in March 2020 to consider all relevant clinical and experimental evidence on the possible utility of intravenous (IV) ascorbate in the treatment of COVID-19-related ARDS. Methods: The panel convened multidisciplinary medical experts and reviewed all relevant in vitro, in vivo, clinical studies and randomized controlled trials on IV ascorbate and issued a consensus report on 23 March 2020 noting that substantial differences in serum concentrations of ascorbate are achieved through IV administration in contrast with the oral route. Findings: The Shanghai panel, and a parallel medical group in Guangzhou, are advising the use of high-dose IV ascorbate for the treatment of ARDS, along with other supportive therapies, including Vitamin D and zinc. We report preliminary progress in using this treatment for 50 consecutive cases treated in Shanghai hospitals, consistent with earlier reports from a meta-analysis of the use of IV ascorbate to treat sepsis. We provide an instructive clinical anecdote regarding a single family where one elderly member with cardiac and other major comorbidities developed and survived ARDS-related sepsis following daily treatments that included 15 g of IV ascorbate. None of her adult caregivers who had ingested between 2 and 10 g of ascorbate daily developed COVID-19.